2019
DOI: 10.16993/sjdr.53
|View full text |Cite
|
Sign up to set email alerts
|

Staff’s and Managers’ Conceptions of Participation for Adults with Profound Intellectual Disabilities or Profound Intellectual and Multiple Disabilities

Abstract: One goal of disability policies in Sweden and other countries is to ensure that people with disabilities are afforded an equal level of daily life participation as other citizens. However, few studies have examined this in adults with profound intellectual disabilities (PID) or profound intellectual and multiple disabilities (PIMD). This study used a phenomenographic approach to interview managers and staff at a social care organisation in a medium-sized Swedish municipality. It aimed to elucidate and describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
2
8
1
Order By: Relevance
“…The results from the observations also show that staff members often draw on their own preferences when making decisions for adults with PI(M)D, which is consistent with the results of earlier research (Dunn et al, 2010; Talman et al, 2019). The results show that staff members did not think the adults with PI(M)D were capable of making decisions, as the staff often made decisions for them.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The results from the observations also show that staff members often draw on their own preferences when making decisions for adults with PI(M)D, which is consistent with the results of earlier research (Dunn et al, 2010; Talman et al, 2019). The results show that staff members did not think the adults with PI(M)D were capable of making decisions, as the staff often made decisions for them.…”
Section: Discussionsupporting
confidence: 89%
“…Although the results from Talman et al (2019) found a lack of definitions and support for the staff members responsible for participation, this study demonstrated that the adults with PI(M)D reached the first three levels of participation. This study's result also shows that staff members work diligently to increase participation with the adults with PI(M)D for whom they care.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Each interview lasted between 10 and 30 min and was conducted in a place decided by the informant. Earlier, these interviews had been used to analyse and problematize the respondents’ conceptions of what participation is for adults with PIMD (Talman, Wilder, Stier, & Gustafsson, ). In the interviews, the opening question was: What does participation mean for adults with PIMD?…”
Section: Methodsmentioning
confidence: 99%